2020
DOI: 10.3390/md18050273
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan Oligosaccharide Fluorinated Derivative Control Root-Knot Nematode (Meloidogyne incognita) Disease Based on the Multi-Efficacy Strategy

Abstract: Plant root-knot nematode disease is a great agricultural problem and commercially available nematicides have the disadvantages of high toxicity and limited usage; thus, it is urgent to develop new nematicides derived from nature substances. In this study, a novel fluorinated derivative was synthesized by modifying chitosan oligosaccharide (COS) using the strategy of multiple functions. The derivatives were characterized by FTIR, NMR, elemental analysis, and TG/DTG. The activity assays show that the derivatives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 42 publications
1
26
0
Order By: Relevance
“…Additionally, chitin is considered a good soil organic amendment that has been widely studied in agriculture due to the fact that it can stimulate the growth of chitinolytic microorganisms and increase their biological control activity to enhance plant protection [7][8][9]. Chitin and its derivatives have been proven to be effective in controlling plant pathogens, including fungi, bacteria, viruses, and nematodes [10][11][12][13]. Chitin is applied to the soil to control nematodes by producing nematicidal substances such as ammonia or regulating the soil microbial community environment.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, chitin is considered a good soil organic amendment that has been widely studied in agriculture due to the fact that it can stimulate the growth of chitinolytic microorganisms and increase their biological control activity to enhance plant protection [7][8][9]. Chitin and its derivatives have been proven to be effective in controlling plant pathogens, including fungi, bacteria, viruses, and nematodes [10][11][12][13]. Chitin is applied to the soil to control nematodes by producing nematicidal substances such as ammonia or regulating the soil microbial community environment.…”
Section: Introductionmentioning
confidence: 99%
“…Next to that, our image-based data show that low nematode infection in AO/DHA-sprayed plants is correlated with increases in Fv/Fm and ChlIdx. Similarly, Fan et al (2020) showed that COS derivatives chitosan-thiadiazole-trifluorobutene (COSSZFB) activate induced resistance against M. incognita in cucumber and simultaneously improved plant growth through accumulation of photosynthetic pigments. Fv/Fm values are known to decrease along with the increasing effect of stresses ( Rolfe and Scholes, 2010 ; Gorbe and Calatayud, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The availability of chemical nematicides commercially have environmental limitations and high toxic for humans. Hence, it was necessary to ind new nematicides derived from natural substances or to develop new strategies for managing PPNs [41].…”
Section: Nematicidal Activity Of Chitosanmentioning
confidence: 99%
“…The nematicidal activity of chitosan and its derivatives hasn'tbeen studied enough. However, there are certain investigations con irmed the activity of chitosan against plant parasitic nematodes [41,[44][45][46][47].…”
Section: Nematicidal Activity Of Chitosanmentioning
confidence: 99%